Brand Image, Awareness And Price Perception Drive Generation Z Purchase Intention : Citra Merek, Kesadaran Merek, dan Persepsi Harga Mendorong Niat Beli Generasi Z - Ramadanti, Arin Oktavia; Rusdianto, R Yuniardi (Academia Open, 2026)
General Background The rapid growth of the fashion industry requires firms to understand consumer behavior, particularly purchase intention as a key indicator of decision-making. Specific Background In the context of local fashion brands, Generation Z consumers exhibit critical and selective preferences shaped by brand-related perceptions. Knowledge Gap Limited empirical evidence examines the combined role of brand image, brand awareness, and price perception in shaping purchase intention for local fashion products within a specific urban context. Aims This study aims to analyze the relationships between brand image, brand awareness, and price perception and the purchase intention of Colorbox products among Generation Z in Surabaya. Results Using a quantitative approach with 100 respondents and multiple linear regression, the findings reveal that all three variables demonstrate positive and significant relationships with purchase intention, both simultaneously and partially, with price perception showing the strongest coefficient. The model explains 61.4% of the variance in purchase intention. Novelty This study provides an integrated empirical assessment of cognitive and perceptual factors influencing purchase intention in the local fashion sector, focusing on Generation Z consumers in an urban Indonesian setting. Implications The findings suggest that local fashion brands should prioritize strengthening brand associations, increasing brand recognition, and maintaining competitive pricing strategies to sustain consumer purchase intention. Highlights: Price-related evaluation shows the highest contribution among examined variables. Brand recognition and association both demonstrate statistically significant relationships. The model accounts for over half of variance in consumer buying tendency. Keywords : Purchase Intention, Brand Image, Brand Awareness, Price Perception, Generation Z